Synergistic pathogenicity of novel duck Orthoreovirus and salmonella typhimurium in ducks - Bing Li; Mingtian Mao; Huihui Li; Xinhong Man; Mian Wu; Chengguang Lu; Meixi Lu; Mengdi Yuan; Zhanbao Guo; Suyun Liang; Zhengkui Zhou; Youxiang Diao; et al. (Poultry Science)
Co-infection with Novel Duck Orthoreovirus (N-DRV) and Salmonella Typhimurium (S. Typhimurium) poses significant threats to duck health. The disease associated with N-DRV is characterized by epizootic outbreaks featuring hepatosplenomegaly, hemorrhage, and necrosis. Ducklings infected with STM primarily exhibit symptoms such as fibrinous pericarditis, perihepatitis, and intestinal hemorrhage. In recent years, China has experienced outbreaks involving mixed infections of these two pathogens in various regions, leading to more complex and atypical clinical manifestations.This study investigated the synergistic effects of these pathogens through animal infection models, histopathological analysis, and quantitative PCR. Antimicrobial susceptibility testing confirmed that the isolated S. Typhimurium strain was multidrug-resistant, complicating therapeutic interventions. Co-infected ducklings exhibited higher mortality rates (up to 26.67 %), earlier peaks in viral replication, and severe clinical symptoms, including diarrhea, reluctance to move, and joint swelling. Viral loads in immune organs such as the spleen, thymus, and bursa of Fabricius were elevated in co-infected groups. Histopathological analysis revealed severe lesions in co-infected ducklings, including liver necrosis, splenic hardening, and intestinal hemorrhages, compared to single infections. Immunological assessments showed suppressed humoral responses in co-infected groups, indicating that N-DRV-induced immunosuppression facilitated bacterial colonization and systemic dissemination. These findings highlight the critical importance of understanding co-infection dynamics and their impact on host-pathogen interactions. This study provides valuable insights for developing integrated control strategies targeting mixed infections in poultry, promoting improved health and sustainable production in the duck farming industry.